Measurement of the top quark mass with lepton+jets final states using $$p$$ p $$p$$ p collisions at $$\sqrt{s}=13\,\text {TeV} $$ s=13TeV - A. M. Sirunyan; A. Tumasyan; W. Adam; F. Ambrogi; E. Asilar; T. Bergauer; J. Brandstetter; E. Brondolin; M. Dragicevic; J. Erö; A. Escalante Del Valle; M. Flechl; et al. (European Physical Journal C: Particles and Fields, 2018)
Abstract The mass of the top quark is measured using a sample of $${{\text {t}}\overline{{\text {t}}}}$$ tt¯ events collected by the CMS detector using proton-proton collisions at $$\sqrt{s}=13$$ s=13 $$\,\text {TeV}$$ TeV at the CERN LHC. Events are selected with one isolated muon or electron and at least four jets from data corresponding to an integrated luminosity of 35.9$$\,\text {fb}^{-1}$$ fb-1 . For each event the mass is reconstructed from a kinematic fit of the decay products to a $${{\text {t}}\overline{{\text {t}}}}$$ tt¯ hypothesis. Using the ideogram method, the top quark mass is determined simultaneously with an overall jet energy scale factor (JSF), constrained by the mass of the W boson in $${\text {q}} \overline{{\text {q}}} ^′ $$ qq¯′ decays. The measurement is calibrated on samples simulated at next-to-leading order matched to a leading-order parton shower. The top quark mass is found to be $$172.25 ± 0.08\,\text {(stat+JSF)} ± 0.62\,\text {(syst)} \,\text {GeV} $$ 172.25±0.08(stat+JSF)±0.62(syst)GeV . The dependence of this result on the kinematic properties of the event is studied and compared to predictions of different models of $${{\text {t}}\overline{{\text {t}}}}$$ tt¯ production, and no indications of a bias in the measurements are observed.